A study of dilute nitride-antimonide semiconductors for near infrared optoelectronics devices - Tan, Kian Hua (2010)
In this thesis, GaNAsSb-based optoelectronic device structures were grown using a solid-source molecular beam epitaxy (MBE) system in conjunction with a radio frequency (RF) plasma N source and Sb valved-cracker source. To reduce the nitrogen plasma induced defects, an ion deflection plate has been installed. Four p-i-n GaNAsSb-based photodetectors have been grown using MBE for photoresponsivity measurement. The devices have shown photo-response up to a wavelength of 1380nm in the spectral response. The device with GaNAsSb layer grown at 350oC shows the highest DC responsivity of 12A/W. This high value of responsivity indicates a carrier avalanche process in the devices, even at reverse bias as low as 1V. In temporal response measurement, the device shows a pulse minimum full-width at half maximum (FWHM) of 40.5ps, corresponding to 3dB cutoff frequency of 4.5GHz. This frequency response is the highest ever reported for dilute nitride-based p-i-n photodetector. Furthermore, high speed data transmission at 5Gb/s has been demonstrated using this GaNAsSb-based p-i-n photodetector at wavelength of 1300nm. To further extend the photo-response from 1380nm to 1600nm, a GaNAsSb-based p-i-n waveguide photodetector has been grown using the molecular beam epitaxy. The device consists of a strained GaNAsSb photon-absorption layer, which has 3.5% of N and 18% of Sb. The device shows photo-response up to at least 1600nm in the spectral response. Moreover, photoresponsivity of 0.29A/W of the device at 1550nm was demonstrated.